(untitled) (Journal of Engineering, 2023)
This study aims to assess the water quality index (WQI) according to the Canadian Council of Ministers of the Environment’s Water Quality Index method (CCME WQI). Four locations (measurement stations) are selected along the Tigris River, in Iraq. Two of them are located in the north near Mosul City, (Mosul Dam and Mosul city), and the other two are located in the south near Al-Amarah city, (Ali Garbi and Al-Amarah). The water data collected is for the period 2011 to 2013, including eleven water quality parameters. These are magnesium (Mg+2), calcium (Ca2+), potassium (K+), sodium (Na+), sulfate (SO42-), chloride (Cl-), nitrate (NO3-), bicarbonate (HCO3-), total dissolved solids (TDS), electric conductivity (EC), and (biochemical oxygen demand BOD5). Results show that the water quality in Mosul city ranged from (83-94) in the two stations, while it has a range of (52-59) in Al-Amarah city for the two sites as well. According to WHO standards, these ranges indicate that the river waterfalls in a good level in Mosul city, while it belongs to the marginal category for Al-Amarah city. This is expected due to the disposal of many pollution sources along the distance from north to south downstream the river, therefore these pollution sources must be controlled.